A KA-PE Transz Kft. logisztikai nehézségei - Varga Dorottya (2017)
The topic of my thesis the logistic activities of a firm called Kaposi International Transport. Having spent my traineeship at this more than 15 year old company I have obtained useful experience in both national and international transport. The company's main activity is transportation but it also deals with warehousing, transporting by trailer and renting out construction equipment. In my thesis I will focus on the logistic activities, mainly national and international transport, and temporary warehousing. During my work at the company I have gained insight in the processes of goods transport that is managed side by side by the company's own and leased fleet. I was also introduced to good handling tools during warehousing and loading. The majority of my thesis is about the issues related to these logistic activities. Most of the problems occur during organizing transport, from the moment of recieving a request till the offloading at the requested address. My aim is to map, describe and react to these issues with possible resolutions. Such issues may contain incorrect information received in the request, the difficulty of agreeing on a fare, organizing transport to fulfil the requirements, or traffic issues during transport. As a closure of my work I have made suggestions on how to solve this problems. I believe the company's workings are financially efficient, however some changes could be introduced to increase efficiency further. Obviously, these improvements would require immediate investment, however the return on investmentwould only need a short time. Amongst my suggesations there is an idea to use a computerized request receipt system, using an interactive board for transparency of rides, as well as building a complete system for warehousing. All in all, I have found that the company works with the right amount of precision and speed. Requestor's needs are satisfied. There are issues in logistics that have no solutions - such as traffic jams or road blocks - but the company makes all possible effort to avoid these. I believe, KA-PE Transz Ltd. is a firm that you can count on.